2011
DOI: 10.1891/0886-6708.26.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence: The Effect of Gender and Contextual Factors on Community Perceptions of Harm, and Suggested Victim and Criminal Justice Responses

Abstract: Using a vignette to depict physical violence by an intimate partner, a 2 (perpetrator gender) X 2 (participant gender) X 2 (frequency) X 2 (intent to cause harm) between subjects factorial design was used to examine under what circumstances individuals perceive: an incident should be illegal, the extent of harm, and appropriate victim and criminal justice responses. There were 868 participants from the Brisbane (Australia) community (48.5% males). The actions of male perpetrators were viewed more seriously and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
0
19
0
7
Order By: Relevance
“…Even more problematic were the men’s experiences within the courts, which are held to an even higher standard in relation to bias, fairness, and checks and balances against injustices. The men’s descriptions of the negative behaviors they experienced within the court systems are consistent with the potential presence of gender-based biases, such as treating men as the primary perpetrators or dismissing the male victim experience (Dennison & Thompson, 2011; Muller et al, 2009). Although some participants in our study reported positive outcomes of their interactions with the courts (e.g., they were granted custody of their children, a restraining order against a female partner, or were acquitted of assault charges), they discussed these positive experiences in terms of luck.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Even more problematic were the men’s experiences within the courts, which are held to an even higher standard in relation to bias, fairness, and checks and balances against injustices. The men’s descriptions of the negative behaviors they experienced within the court systems are consistent with the potential presence of gender-based biases, such as treating men as the primary perpetrators or dismissing the male victim experience (Dennison & Thompson, 2011; Muller et al, 2009). Although some participants in our study reported positive outcomes of their interactions with the courts (e.g., they were granted custody of their children, a restraining order against a female partner, or were acquitted of assault charges), they discussed these positive experiences in terms of luck.…”
Section: Discussionmentioning
confidence: 59%
“…According to those who support the gender-based paradigm of IPA, professionals, such as police and court agents, are influenced by traditional societal norms and views on IPA as almost exclusively perpetrated by males against females in the defense of the patriarchy (Dutton, 2010). Indeed, the literature on public opinion suggests that the same actions are viewed more seriously when perpetrated by males and that victims are more often encouraged to seek help when the perpetrator is male (e.g., Dennison & Thompson, 2011). As such, male victims are rarely viewed by society and the professionals within the CJS as “appropriate victims.” This cultural stigma is thought to impact self-stigma, leading to the individual having concerns about negative treatment, rejection and disapproval from others, and internalized negative beliefs about IPA as true of the self (e.g., I must not be a “real man”; Overstreet & Quinn, 2013).…”
mentioning
confidence: 99%
“…Men are much less likely to access help from support services in general (Addis & Mahalik, 2003), possibly leading to a greater number of women seeking help, and in turn, less visibility of male victims of IPV. The abuse can also be as severe as the abuse experienced by female victims from male partners, however, because men are less likely to incur serious injuries from the abuse, their experience is not always perceived as serious (Dennison & Thompson, 2011;Nowinski & Bowen, 2012).…”
Section: Researchedmentioning
confidence: 99%
“…Attitudes about IPV (particularly IPV toward women) have been examined to better understand the underlying causal factors for IPV involvement (Flood & Pease, 2009), and this focus includes global assessments of attitudinal influence (Dennison & Thompson, 2011; Kiss et al, 2015; Lin, Sun, Wu, & Liu, 2016; Nayak, Byrne, Martin, & Abraham, 2003; Yount et al, 2014). For example, men who are involved in IPV overestimate the prevalence of IPV and have skewed social norms (Neighbors et al, 2010).…”
Section: Violence Attitudesmentioning
confidence: 99%
“…Gender differences in attitudes about IPV and about violence have been found in several studies (Bryant & Spencer, 2003; Sylaska & Walters, 2014; Temple, Shorey, Tortolero, Wolfe, & Stuart, 2013). For example, previous research shows that, when examining citizens’ perceptions of IPV, male perpetrators’ actions were thought more serious, compared with female perpetrators’ actions, and victims were recommended to seek more assistance when the perpetrator was male (Dennison & Thompson, 2011). Moreover, men differ in initiation of IPV (Henning & Feder, 2004) and in attitudes about IPV (Kane, Staiger, & Ricciardelli, 2000).…”
Section: Gender Differencesmentioning
confidence: 99%